Restoring phosphorus from water to soil: Using calcined eggshells for P adsorption and subsequent application of the adsorbent as a P fertilizer - Lee, Jae In; Kim, Jeong Man; Yoo, Soo Cheul; Jho, Eun Hea; Lee, Chang Gu; Park, Seong Jik (Chemosphere, 2022)
This study investigated the solution for two environmental issues: excess of P in water and its deficiency in soil, which is restored by transferring the adsorbed P from water into the soil using eggshell as an adsorbent. The eggshells were calcined at different temperatures to improve their adsorption capacity, and evaluated for their physical/chemical properties and P adsorption capacity. The eggshells calcined at 800 °C (CES-800) had the highest P adsorption; CaCO3 decomposed into 23.6% of CaO and 40.8% of Ca(OH)2, eluting more Ca that reacted with soluble P in water. X-ray diffraction analysis confirmed that CES-800 removed P as hydroxylapatite by reacting with Ca. Pseudo-first-order and Langmuir models suitably described the kinetic and equilibrium of P adsorption by CES-800, respectively. The maximum adsorption capacity of CES-800 was 108.2 mg g−1. As the solution pH increased from 3 to 11, the adsorption amount decreased from 99.8 mg g−1 to 62.3 mg g−1. The feasibility of CES-800 as a filter medium was assessed using real lake water under dynamic flow conditions; > 90% of P removal was achieved at 158 h, and the P adsorbed was 11.5 mg g−1. When CES-800 and P adsorbed CES-800 (P-CES-800) were applied to the soil at the studied rates, the earthworms were unaffected by toxicity, suggesting the use of both adsorbents in soil without adverse effects. The shoot fresh weight, tiller number, and total dry weight significantly increased in P-CES-800 applied rice plants compared to the control plants, indicating that P-CES-800 can be a good alternative to conventional P-fertilizer in rice cultivation.
Keywords: Adsorption capacities; Bioluminescent bacteria; Earthworm; Eggshell; Environmental issues; P fertilizers; Phosphorus removal; Physical-chemical properties; Rice cultivation; Soluble P; Adsorption; Animals; Egg Shell; Fertilizers; Hydrogen-Ion Concentration; Kinetics; Phosphorus; Soil; Water; Water Pollutants, Chemical; Bioluminescent bacteria; Calcination; Earthworm; eggshell; Phosphorus removal; Rice cultivation